2016
DOI: 10.1111/jth.13340
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia exacerbates Alzheimer's disease pathology by way of the β‐amyloid fibrinogen interaction

Abstract: Summary Background Accumulating clinical evidence suggests that hyperhomocysteinemia (HHC) is correlated with Alzheimer’s disease (AD) and vascular dementia. Objective This study was carried out to elucidate the specific role of elevated homocysteine (HC) levels in AD pathophysiology. Methods Immunohistochemistry was used to examine amyloid-beta (Aβ) deposition along blood vessels, also known as cerebral amyloid angiopathy (CAA), fibrin(ogen) deposition, and their correlation to each other in the brains o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 59 publications
2
46
0
Order By: Relevance
“…For instance, an imbalance of this metabolic pathway, marked by hyperhomocysteinemia and/or an altered SAM/SAH ratio, is a hallmark of memory loss and cognitive decline in elderly populations [34, 35] This loss of metabolic homeostasis may result from deficiency in metabolites and co-factors—such as vitamin B 12 or folic acid—directly and indirectly involved in the methylation of homocysteine. An increased interest exists to decipher their role as potential biomarkers of neurodegeneration in Alzheimer’s disease [3638]. The robustness of our method for the sensitive detection and quantitation of the 17 metabolites and co-factors of methionine metabolism was assessed in biological materials collected from healthy donors and patients diagnosed with Alzheimer’s disease.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, an imbalance of this metabolic pathway, marked by hyperhomocysteinemia and/or an altered SAM/SAH ratio, is a hallmark of memory loss and cognitive decline in elderly populations [34, 35] This loss of metabolic homeostasis may result from deficiency in metabolites and co-factors—such as vitamin B 12 or folic acid—directly and indirectly involved in the methylation of homocysteine. An increased interest exists to decipher their role as potential biomarkers of neurodegeneration in Alzheimer’s disease [3638]. The robustness of our method for the sensitive detection and quantitation of the 17 metabolites and co-factors of methionine metabolism was assessed in biological materials collected from healthy donors and patients diagnosed with Alzheimer’s disease.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the rate of cognitive decline positively correlated with the increased level tHcy in patients with the moderate stage of Alzheimer’s disease and they have stronger behavioral disturbances which could be associated with major depressive disorder [81,82]. Very recently was shown, that Hcy and Hcy-TL enhance the interaction between fibrinogen and amyloid β, promote the formation of tighter fibrin clots and delay clot fibrinolysis [83]. It has been also reported that dysfunctional folate-methionine pathway enzymes, mostly MTHFR polymorphisms C677T and A1298C, may play an important role in the pathophysiology of autism (MIM 209850) [84,85].…”
Section: Hyperhomocysteinemia and Diseasesmentioning
confidence: 99%
“…Homocysteine may be remethylated to methionine or converted to cysteine by the transsulfuration pathway. In triple transgenic mice, a high level of homocysteine increased brain b‐amyloid (Ab) levels and tau neuropathology and induced memory deficits (Li et al, 2014; Chung et al, 2016). Sevoflurane can disrupt methionine and cysteine metabolism, increasing beta‐amyloid and tau levels, eventually leading to neurological damage.…”
Section: Oxidative Stressmentioning
confidence: 99%